Narrador, ambivalência e ironia em Iaiá Garcia, de Machado de Assis - Machado, Raquel Andrade (2017)
The present research aims at analyzing the role of the narrator in Iaiá Garcia (1878), by Machado de Assis, on the threshold between reliability and unreliability, aspiring to ambivalence and irony. Pointed by the critical tradition as an in-between novel from the author’s romantic and realist phases, the question that guides this research is that of investigating whether, and to which extent, it would be possible to detect in the narrative structure, especially in the narrator’s point of view, this transitional place between the two aesthetic-literary paradigms by observing the characters Iaiá Garcia, Estela and Jorge – which form the amorous triangle in the plot. We assumed the hypothesis that the narrator has a preponderant role in the construction of the narrative by positioning itself halfway between omniscience and loss of control over the characters, by conveying a dialogic discourse that highlights irony. Furthermore, this is what we could call a chess-player narrator, one who condones the female characters’ – Estela and Iaiá – moves in the chess game; one who detaches itself from the enunciation to the enunciated – chapter XII –, and one whose focus is on the amorous triangle Estela-Jorge-Iaiá – the chess piece used by the ironist narrator to criticize romantic love, with its excesses and fanciful idealizations, and to project another sort of love, driven by reason and logic. As theoretical underpinning, we used Wayne C. Booth (1964) on the telling-showing distinction and on the types of narration; Mikhail Bakhtin (2011) on polyphony, alterity and dialogism, as well as Linda Hutcheon (2000) and her studies on irony. The analysis of the narrative discourse showed that the narrator’s detachment lies upon strategies of telling and showing, applied to interval tones whether of free indirect discourse or irony. Thus, it is possible to observe the existence of a literary project thought by Machado de Assis, which sets new paradigms regarding the narrator’s position, often distrusted in the omniscient mode; the creation of characters, made more autonomous and responsible for their viewpoints; and finally, the reader, from whom the reading will require more than fondness for Romanesque adventures, typical of feuilleton novels